Misguided and Modest: Reflections of Our Youth Voice Research - Stride, Annette; Brazier, Ruth; Fitzgerald, Hayley (Frontiers in Sports and Active Living, 2022)
In recent years, Physical Education (PE) has seen a growth in the commitment to youth voice research. This approach foregrounds the practice of researching with young people, rather than conducting research on or about them. Whilst we are cognisant of the possibilities youth voice research offers, we are also concerned that there is a tendency to overlook the challenges of supporting youth voice activities (Holland et al., 2010; McNamara, 2011; Fox, 2013; Jones and Bubb, 2020; Finneran et al., 2021). As James (2007, p. 270) argues, by reflecting on “the complexities of the issues that frame what children say, rather than offering the simple message that recording and reporting their voices is sufficient, it may be that children’s voices will be more willingly listened to and their perspectives more readily understood”. This paper draws on our collective reflections to bring to the fore some of the complexities we have encountered when attempting school-based youth voice research. We explore the following questions: How can youth voice research engage with different young people to capture a diversity of voices? What are the challenges of undertaking youth voice research? What are the possibilities of change through youth voice research? We consider these questions by drawing on Robinson and Taylor’s (2007) four principles of student voice work: communication as dialogue; participation and democratic inclusivity; unequal power relations; change and transformation. We use these principles to critique our own research and, in doing so, draw on entries from our research diaries. The paper questions whether young people need help to share their experiences about PE, or whether it is researchers, teachers and schools who need help to more readily recognise and be attentive to young people's voices. We point to the importance of recognising modest change through youth voice research and the need to secure adult allies to support activities and outcomes. Engaging in youth voice research is an immersive and messy encounter and yet we remain firm advocates of youth voice work. This paper offers a starting point for others to begin to grapple with the pitfalls and possibilities when supporting youth voice research.